PHOSPHONIC ACID MODIFICATION TO MOLYBDENUM ATOM CATALYST FOR CO2 HYDROGENATION ON MAGNESIUM HYDRIDE SURFACE - Gumawa Windu Manggada; Shixue Zhou (DISTILAT: Jurnal Teknologi Separasi, 2022)
Catalytic hydrogenation is one of the most effective ways to convert CO2 to high value-added chemicals, and it is challenging to improve the catalytic activity and product selectivity based on the understanding of catalysis mechanism of the process. In this work, organic phosphonic acid was innovatively employed to tune single atom catalyst for CO2 hydrogenation to methanol, and the effect of fluoromethylphosphonic acid (FMPA) on the electronic structure of molybdenum and the reaction energy barriers of CO2 hydrogenation on MgH2 surface were investigated by density functional theory (DFT) calculations. The results showed that the reaction energy barriers at the key steps were significantly decreased by the introduction of FMPA, which stabilized the reaction intermediates from CO2 hydrogenation by reducing the electron density of molybdenum adsorption site with its oxygen atoms. The reverse water gas shift (RWGS) pathway was superior to formate pathway for CO2 hydrogenation on FMPA/Mo-MgH2(001) surface with energy barrier only 1.22 eV at the rate-determining step, and CH3OH was the overwhelming product rather than HCOOH, H2CO, CO or CH4 considering the reaction barriers and adsorption energies. The combination of organic phosphonic acid with single atom catalyst can generate the rational design of new catalytic system, which is helpful to control the reaction pathway and product selectivity.